ANALISIS KESESUAIAN LAHAN PERMUKIMAN DI KAWASAN PERKOTAAN KOTA SAMPIT KABUPATEN KOTAWARINGIN TIMUR - Janthy Trilusianthy Hidayat; M. Yogie Syahbandar; M. Jamalul Ihsan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The Urban Area of Sampit City is a growth center in East Kotawaringin Regency which will require increased land and must be suitable in supporting the development of settlement areas. The urban area of Sampit City consists of 3 (three) sub-districts, namely Baamang District, Mentawa Baru Ketapang District, and Seranau District. The aims of study were to analyze land capability, land availability and land suitability in the Sampit City Urban Area, and identify the level of land suitability for settlement areas in the Sampit City Urban Area. The analytical method uses descriptive quantitative analysis including analysis of land capability units, analysis of land availability and suitability. The results of the analysis show that the land capability in the Urban Area of Sampit City consists of three classes of development capabilities, namely high, medium and low. The availability of land results in the distribution of land allotments that can be built as residential areas 26.190 Ha covering a medium land suitability level and high land suitability.